The normal microbiota of the ocular surface and the connection between the changes in its composition and ophthalmic pathologies - G. N. Rezbaeva; O. I. Orenburkina; I. A. Gimranova; A. E. Babushkin; G. R. Gazizullina (Российский офтальмологический журнал, 2024)
The microflora of the ocular surface serves an important role in the protective mechanisms, since it significantly affects the regulation of immunological activity and the barrier effect against pathogen invasion. The presence of a healthy ocular microbiome causes no eye diseases, and ophthalmic pathologies develop only when anatomical barrier functions and immune status are violated. A healthy eye surface is characterized by a relatively stable and small microbiome diversity. The environment, diet, gender, age and some other factors, such as potential contamination, affect the composition of the microbial flora, complicate its analysis and may affect the results of the latter. Moreover, potentially pathogenic organisms various disorders, including inflammation and methods of treating ocular surface can also affect the composition of eye microbioma. Traditional microbiological studies based on cultivation often reveal a rather low diversity of microorganisms in a particular region. New research methods, e.g. genetic analysis based on rRNA sequencing, indicate a much greater diversity than previously assumed. It has been shown that changes in the microbiota composition occur in blepharitis, conjunctivitis, keratitis, uveitis, dry eye syndrome, age-related macular degeneration, diabetic retinopathy, glaucoma, myopia, etc.Currently, there are no clear criteria for describing norms of the ocular microbiome (including fluctuations which should be considered normal during life). The features and impact of the microflora composition on immunity and human body as a whole, in particular, those associated with the intestinal microbiome and their dependence on gender, age, place of residence, etc have not been studied in full.Further studies of eye microbiome can give answers to all these questions.